Pengaruh Hedonisme Influencer di Media Sosial Terhadap Perilaku Konsumtif Generasi Z di Daerah Istimewa Yogyakarta - Muhammad Lukman Hakim (Jurnal Mutakallimin : Jurnal Ilmu Komunikasi, 2026)
Social media no longer functions merely as a means of interpersonal communication; instead, it creates a cultural ecosystem where trends, lifestyles, and self-identities are continuously reproduced and disseminated on a global scale. One of the most powerful manifestations of this transformation is the emergence of the "influencer" phenomenon. The presence of influencers marks a paradigm shift from one-way communication toward peer-to-peer marketing. The hedonistic attitude of influencers within the context of social media refers to the tendency of individuals to showcase lifestyles oriented toward pleasure, luxury, and material achievement. Generation Z is the demographic group most active and vulnerable to this phenomenon, as they utilize social media not only as a form of entertainment but also as a primary source for social learning and lifestyle references. The purpose of this study is to determine the influence of influencer hedonism on the consumptive behavior of Generation Z in the Special Region of Yogyakarta. The method used in this research is quantitative. The sampling technique employed is purposive sampling. Data collection instruments were distributed both online via the Google Form platform and offline to reach Generation Z respondents across the Special Region of Yogyakarta. The data analysis technique utilized Simple Linear Regression. The results of the study indicate that, partially through the T-Test, influencer hedonism significantly influences the consumptive behavior of Generation Z in the Special Region of Yogyakarta.